Enhancing science communication skills biology in students through the number head together - Ismirawati, Nur; Amri; Randi, Nur Zakiyah; Kasmawati (Universitas Negeri Jakarta, 2024)
The teaching of science communication skills at the high school level can be effectively accomplished through lessons that are oriented not only towards the development of cognitive skills, but also towards the acquisition of hands-on communication skills. The present study employs an experimental research design to investigate the impact of NHT-type cooperative learning on students' science communication skills. This study employs an experimental design comprising an class and a control class. The study population comprised students at X MIPA UPT SMAN 2 The X MIPA 3 class was designated as the experimental class, while the X MIPA 7 class served as the control class. Sampling was conducted using a randomised system. The data employed in this study were derived from two sources: primary data collected via the science communication skills rubric and secondary data obtained through observation of student and teacher activities. The data collection instrument was a science communication skills observation sheet that had previously been tested for validity and reability. The data were analysed using the Friedman test, which revealed significant differences in students' science communication skills between the control and experimental classes at each meeting (p < 0.05). Similarly, the Wilcoxon test demonstrated a significant difference between the control and experimental classes at each meeting (p < 0.05). The findings of this study suggest that further research should be conducted at a larger scale to gain a more comprehensive understanding of the rubric of science communication skills.